True Leadership Leadership Styles and the Kenotic Relationship - Peltz, David P.; Wilson, John H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This edited collection addresses several forms of moral leadership within the context of kenosis, bringing together both secular and biblical perspectives on the role of morality and self-sacrifice in effective leadership theory and practice. The contributors apply various leadership theories in the analysis of sacred texts in order to uncover unique insights into the biblical truth about leadership. Their analysis moves away from egotistical leadership focused on self-aggrandizement and provides a new model for leadership - one characterized by morality, authenticity, and service. True Leadership will benefit scholars, researchers, and students interested in values-based leadership and seeking to enrich their understanding of organizational behavior and leadership development.
1. True Leadership: Beyond the Shadows -- 2. Distinguishing Between Servant Leadership and Authentic Leadership -- 3. The Mind of the Transformational Leader -- 4. The Character of a Leader: Authenticity as a Moral Distinction -- 5. Transformed to Authenticity: Where a Leader$1 (Bs History Meets Destiny -- 6. Authentic Leadership Development in the Life of Moses -- 7. Leadership Development: The Role of Learning in the Authentic, Transformational, Servant, and Kenotic Leader -- 8. The Impact of Kenosis on the Transformational Authentic Leader -- Final Thoughts. .s
Keywords: Management; Personnel management; Business ethics; Employees$1 (BCoaching of.s; Management; Human Resource Management; Business Ethics; Coaching